Big Nate's greatest hits - Peirce, Lincoln (Peirce, Lincoln. Big Nate (Comic strip), 2015)
The more Big Nate, the better! Readers will have their fill of Nate's wisecracks and school-day shenanigans in this giant collection of hilarious comic strips.